2022
DOI: 10.1007/jhep11(2022)088
|View full text |Cite
|
Sign up to set email alerts
|

Supersizing axions with small size instantons

Abstract: We construct a new framework to calculate the enhancement of axion masses and concomitant effects on axion-meson mixing arising from small size instantons (SSIs), which originate in models featuring an extended color gauge symmetry. The framework is based on an explicit evaluation of ‘t Hooft determinantal operators that partition into instanton amplitudes, affording a more precise determination of the axion-diphoton coupling than previous results. Using an explicit model first presented in ref. [1], we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Using the spurion argument (see Refs. [17,18]), we can now observe that below the scale of QCD confinement, instantons induce a periodic potential for the axion leading the axion field to acquire a tadpole offset that minimizes the overall vacuum energy and adjusts the Θ parameter to zero:…”
Section: The Strong Cp Problem In the Standard Model And The Axion So...mentioning
confidence: 94%
“…Using the spurion argument (see Refs. [17,18]), we can now observe that below the scale of QCD confinement, instantons induce a periodic potential for the axion leading the axion field to acquire a tadpole offset that minimizes the overall vacuum energy and adjusts the Θ parameter to zero:…”
Section: The Strong Cp Problem In the Standard Model And The Axion So...mentioning
confidence: 94%
“…For an ALP, χ remains a free parameter, while a vanilla QCD axion has χ = χ QCD , although recent studies have demonstrated that χ can be enhanced by non-QCD sources and still preserve the axion solution to the strong CP problem [38][39][40][41]. As long as λ AB is sufficiently large, the basis rotation in eq.…”
Section: Jhep03(2023)078mentioning
confidence: 99%
“…Since we focus on the parameter space where the ALP mass m a > 1 MeV for which the canonical QCD axion is disfavored, we must keep the SM fermions and anomalons dynamical in loop functions. In particular, recent literature has emphasized the collider scale in context of high-quality axions, where the axion is buffered from UV effects and the topological susceptibility is enlarged [41,[78][79][80][81][82][83]. The expression for G aγγ , defined previously in eq.…”
Section: Constraints On Alpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related work to solving the strong CP problem departing from the canonical band include Refs. [3][4][5][6][7][8][9][10][11]. Furthermore, the new parameter space corresponds to an almost perfect alignment between the soft breaking vacuum and the θ QCD vacuum.…”
mentioning
confidence: 93%